T Helper Cell Subsets in Clinical Manifestations of Psoriasis. (10th August 2016) - Diani, Marco; Altomare, Gianfranco; Reali, Eva
Abstract : Psoriasis is a chronic inflammatory skin disease, which is associated with systemic inflammation and comorbidities, such as psoriatic arthritis and cardiovascular diseases. The autoimmune nature of psoriasis has been established only recently, conferring a central role to epidermal CD8 T cells recognizing self-epitopes in the initial phase of the disease. Different subsets of helper cells have also been reported as key players in the psoriasis pathogenesis. Here, we reviewed the knowledge on the role of each subset in the psoriatic cascade and in the different clinical manifestations of the disease. We will discuss the role of Th1 and Th17 cells in the initiation and in the amplification phase of cutaneous inflammation. Moreover, we will discuss the recently proposed role of tissue resident Th22 cells in disease memory in sites of recurrent psoriasis and the possible involvement of Th9 cells. Finally, we will discuss the hypothesis of a link between T helper cell subsets recirculating from the skin and the systemic manifestations of psoriasis.